Implicit and Explicit Language Learning to Facilitate Subordinating Conjunction in Developmental Language Disorders - Taruna, Rexsy Taruna (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Abstract Background: Priming and recast approaches are scientifically proven to improve grammatical production abilities. However, based on a literature review, there are no articles that test the effectiveness of the priming and recast approach in improving grammatical skills such as subordinating conjunctions. Objectives: This study aims to see the effectiveness of the priming and recast approach in improving subordinating conjunctions in children with developmental language disorders. Methods: This research uses a quasi-experiment, with multiple baseline across behaviors design. This research involved two children diagnosed with developmental language disorders aged 5 years. Each participant was trained to use subordinating conjunctions for five sessions, 30 minutes per session Results: In general, the priming and recast approach can improve the ability of subordinating conjunctions in children with developmental language disorders. Conclusion: Grammatical production of subordinating conjunctions can be trained using implicit or explicit learning. Keywords : priming, recast approach, language disorder, speech therapy, subordinating conjunctions